Efficacy of Fungi in the Decolorization and Detoxification of Remazol Brilliant Blue Dye in Aquatic Environments - Nabeela; Sumera Afzal Khan; Saadat Mehmood; Sohaib Bin Shabbir; Sajid Ali; Abdulwahed Fahad Alrefaei; Mohammed Fahad Albeshr; Muhammad Hamayun (Microorganisms, 2023)
Industrial effluents result in water pollution and affect the biological activity of aquatic and terrestrial life. In this study, efficient fungal strains were isolated from the aquatic environment and identified as Aspergillus fumigatus (SN8c) and Aspergillus terreus (SN40b). The isolates were selected based on their potential to efficiently decolorize and detoxify Remazol brilliant blue (RBB) dye, which is extensively used in different industries. Initially, a total of 70 different fungal isolates were screened. Among these, 19 isolates demonstrated dye decolorization capabilities, and SN8c and SN40b revealed the highest decolorization capabilities in liquid medium. The maximum estimated decolorization for SN8c was 91.3% and for SN40b, 84.5% at 40 mg/L of RBB dye in the presence of glucose (1 gm/L), after 5 days of incubation at different levels of pH, temperature, nutrient source, and concentration. RBB dye decolorization using SN8c and SN40b isolates was at a maximum of 99% at pH 3–5, whereas minimum decolorization was recorded as 71.29% and 73.4% SN8c, respectively, at pH 11. The maximum decolorization of the dye was 93% and 90.9% in a defined glucose concentration of 1 gm/L, and a 63.01% decrease was recorded in the decolorization activity at a low level of glucose concentration (0.2 gm/L). Finally, the decolorization and degradation were detected using UV spectrometry and HPLC. Toxicity tests of pure dye and treated dye samples were checked against the seed germination of different plants and the larvae mortality of Artemia salina. This study revealed that indigenous aquatic fungal flora can recover contaminated sites and support aquatic and terrestrial life.